Asylum migration to OECD countries: What are the motives and drivers of asylum migration and how strong are they? - Felicitas Nowak-Lehmann D.; Adriana R. Cardozo; Inmaculada Martínez-Zarzoso; Sarah Frohnweiler (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2022)
In this study we analyse different motives for asylum, focussing on the relative strength of specific asylum reasons and concentrating on origin and destination countries of special relevance. To this end, we build a bilateral asylum migration model, use panel data techniques based on a panel of 131 origin/sending countries and 37 OECD countries over a maximum period of 22 years, and apply the High Density Fixed Effect (HDFE) Poisson Pseudo Maximum Likelihood (PPML) estimation technique. Our model includes the economic situation in both sending and receiving countries; political factors in sending countries, such as the political terror scale, civil liberties, government stability, military in politics; institutional factors, such as law & order; personal safety aspects, such as ethnic tensions, external conflict, internal conflict, and religious tensions. We find that economic factors influence asylum claims to a certain extent. Moreover, we identify only deteriorations in civil liberties, internal conflict and ethnic tensions as triggers of increased asylum demand among the personal safety aspects. As to relevant sub-samples of origin countries, a deterioration in civil liberties and an aggravation in ethnic tensions lead to a more than proportionate increase in asylum migration from major asylum seeking countries and a worsening of conflict leads to an extremely strong reaction in asylum requests from refugees of conflict-ridden countries. While these reactions are plausible, they are far less pronounced in the overall sample. As to the question which destination country can be chosen as safe haven, empirical evidence shows that bilateral recognition rates signal bilateral attractiveness in a brutally honest way.
Keywords: C23; F22; J15; J61; 330; asylum migration; motives; identification of relevant relations; bilateral recognition rates; high density fixed effect poisson pseudo maximum likelihood technique